IPTEK bagi masyarakat (IbM) kelompok petani ikan di Desa Eris, Kecamatan Eris, Kabupaten Minahasa - Sinjal, Hengky J; Watung, Juliaan Ch (Universitas Sam Ratulangi, 2015)
The purpose of this community service in term of IbM was to transfer the aquaculture technology such as sex reversal, immunostimulant, feed formulation and financial management training to fish farmer at Eris Village. The methods used included elucidation, explanation, training and field practice. The results showed that fish farmers actively participated in discussion and practicing the given subjects.Â In addition, farmers were able to increase their skill and knowledge about how to produce male fish fingerling, how to formulate fish feed and immunostimulant and how to manage their financial. Products resulted through this service were appropriate according the standard criteria. Continuous guidance from university and government is required to ensure the success of this service activity. Â Keywords: fish farmer, sex reversal, immunostimulant, fish feed, financial management, Eris Village